COMPARATIVE ANALYSIS OF INTERLANGUAGE ERRORS MADE BY JUNIOR HIGH SCHOOL AND SENIOR HIGH SCHOOL - Lilik Nuraini (Jurnal Pedagogy, 2017)
This study deals with the comparative analysis of interlanguage errors made by Junior High School and Senior High School. The objective of this research is to identify the types of interlanguage errors made by the Junior High School and Senior High School. The similarities and the differences of interlanguage error made by Junior High School and Senior High School, and the extend do the native language and the target language influence the student interlanguage system. The data are students’ errors in writing. The erroneous sentences are taken from 40 pieces of the junior high school students’ writing, and 40 pieces of the senior high school students’ writing. The data analyzed qualitatively, especially in using Error analysis Framework. The results indicate that the interlanguage errors made by Junior High School and Senior High School have the similarities and differences. The similarities of interlanguage errors that found by researcher are: wrong spelling of word, the use of Indonesian word, and omission of bond morpheme‘s/es’ as the plural marker. The researcher found ‘the wrong spelling of word, the use of Indonesian word, and omission of bond morpheme ‘s/es as the plural marker” in Junior High School, in Senior High School composition. The differences of interlanguage error made by Junior High School and Senior High School as follow: the use of V-ing for past event in Junior High school, it is not found in Senior high school composition. The errors that found in Senior High School, such as: False friend, Additional apostrophe (’s) is not appropriate, Additional‘s’ as Singular Marker, Omission of preposition, The use of singular noun for plural noun, The use of subjective pronouns for objective pronouns, and Omission of Article (a,an,the) , these errors are not found in Junior High School composition. There are two influences in students’ English namely influenced by first language and influenced by target language; the most dominant influence in students’ interlanguage in Junior high school and Senior high school is influenced by the target language. It can be seen from the percentages of it, 85, 71% in Junior High School and 85, 71% in Senior High School composition.